Beyond Infrastructure: Personnel Capability, Power Reliability, and the Social Production of Operational Effectiveness in Border Security - Suhardiyanto, I Wayan Agus; Hasudungan, Ferdinand; Ramsi, Oktaheroe (KOMUNITAS: Jurnal Ilmu Sosiologi, 2026)
This study examines border security operational effectiveness beyond technological determinism by emphasizing its social production through personnel capability and power system reliability. Challenging policy and technical discourses that privilege infrastructure as the primary driver of performance, the study conceptualizes effectiveness as a socio-technical outcome shaped by the interaction of technology, human skills, and organizational conditions in geographically isolated regions. Using a quantitative explanatory design, data were collected from 185 personnel of outer island security task forces under Kodam XV/Pattimura. Hybrid satellite communication utilization, personnel capability, power system reliability, and communication–electronic effectiveness were measured through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that personnel capability exerts a strong and significant positive effect on operational effectiveness, whereas communication technology and power reliability display no significant direct effects when considered independently. However, their simultaneous interaction generates a substantial synergistic effect, explaining over 80% of the variance in effectiveness. These results indicate that infrastructure and energy systems function primarily as enabling conditions, while performance emerges from the capacity of personnel to translate technological potential into coordinated organizational action. The study contributes to socio-technical systems theory, extends organizational sociology to security institutions, and provides rare empirical evidence from peripheral state contexts in the Global South.